The effect of question-answer relationship (QAR) strategy on students' reading interest and reading comprehension ability - Nur Anisa Utami; Sulfasyah; Tarman A. Arief (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study aims to describe fourth-grade elementary school students' reading interest and reading comprehension ability through the Question Answer Relationship (QAR) strategy. This type of research is quasi-experimental with a nonequivalent control group design. The research sample was fourth-grade students at SD Inpres Bontoala I Gowa, totaling 60 students. Data on reading interest was collected through a questionnaire technique, and reading comprehension ability was assessed using a test technique. The collected data were analyzed through descriptive and inferential analysis techniques consisting of independent sample t-tests and Manova tests. The results showed an increase in students' average reading interest and reading comprehension ability through the QAR strategy, so it can be concluded that the QAR strategy can increase the reading interest and reading comprehension ability of fourth-grade students of SD Inpres Bontoala I Gowa.